Inovasi Seni Ramah Lingkungan: Workshop Eco Print untuk Masyarakat Brebes - Isrotun Ngesti Utami; Bayu Widiyanto; Muriani Nur Hayati (Universitas 45 Surabaya, 2025)
This community service activity aims to introduce and train the Brebes community in utilizing eco print techniques as a form of environmentally friendly art innovation. Eco print is a method of printing natural patterns using leaves, flowers, and other organic materials that are environmentally friendly, so it can be a sustainable alternative in the creative industry. Through this workshop, participants were invited to understand the process of making eco print, starting from the selection of materials, dyeing techniques, to waste management. The implementation method included counseling, demonstration, and hands-on practice by the participants. The evaluation results showed an increase in community understanding and skills in utilizing surrounding natural resources to create products with economic value. This activity not only encourages creativity but also increases awareness of the importance of environmental conservation. Hopefully, in the future, the people of Brebes can develop eco print-based businesses to support a sustainable local economy.